Combining high activity with broad monomer scope: indium salan catalysts in the ring-opening polymerization of various cyclic esters. Issue 10 (13th April 2022) - Bruckmoser, Jonas; Henschel, Daniel; Vagin, Sergei; Rieger, Bernhard
Abstract : An indium salan-type catalyst shows very high activities in the ring-opening polymerization of various cyclic esters, including β-butyrolactone, γ-butyrolactone, lactide, ε-caprolactone and ε-decalactone. Abstract : Combining high catalytic activity with broad monomer scope is an appealing yet challenging task in polymerization catalysis. Examples of such all-rounder catalysts in the ring-opening polymerization (ROP) of lactones are rare. Herein we report an indium alkoxide complex supported by a salan-type framework that shows very high rates, excellent control and high tolerance against chain transfer agents in the ROP of several cyclic esters yielding high molecular weight (bio)degradable polymers. Additionally, by using propylene oxide as solvent, poorly active but air-stable indium chloro pre-catalyst can be converted in situ into a catalytically active species with drastically enhanced polymerization rates. In contrast to the salan-type initiator, a related indium alkoxide catam-type complex shows reduced activity in ROP of β-butyrolactone, ε-caprolactone, ε-decalactone and lactide, highlighting the importance of framework flexibility in catalyst design.